1997
DOI: 10.1002/(sici)1522-7189(1997)5:6<255::aid-nt6>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic evaluation of Yessotoxin

Abstract: Yessotoxin (YTX), originally found in association with diarrhetic shellfish poisoning (DSP), caused neither intestinal fluid accumulation nor inhibition of protein phosphatase 2A. Orally, YTX was not lethal to mice at 1.0 mg/kg. The toxin showed weak cytotoxic and antifungal activities. Neither hemolytic nor ichthyotoxic effect was observed. Nat. Toxins 5:255–259, 1997. © 1998 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
77
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 1 publication
0
77
0
Order By: Relevance
“…Animal studies indicate that PTXs and YTXs are much less toxic via the oral route and that they do not induce diarrhea. [13][14][15][16] PTXs and YTXs have recently been eliminated from the definition of DSP toxins. The mouse bioassay (MBA), which is the official testing method of DSP in Japan and many countries, also detects PTXs and YTXs, resulting in false positives for OA/DTX analogues.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies indicate that PTXs and YTXs are much less toxic via the oral route and that they do not induce diarrhea. [13][14][15][16] PTXs and YTXs have recently been eliminated from the definition of DSP toxins. The mouse bioassay (MBA), which is the official testing method of DSP in Japan and many countries, also detects PTXs and YTXs, resulting in false positives for OA/DTX analogues.…”
Section: Introductionmentioning
confidence: 99%
“…These natural compounds are included among algal toxins because i.p. injection of yessotoxin into mice leads to death at doses as low as 80 mg kg À1 (Murata et al, 1987;Ciminiello et al, 1997;Ogino et al, 1997). As YTXs can be accumulated in edible molluscs, such as scallops and mussels (Murata et al, 1987;Ciminiello et al, 1997), by filter feeding, the current European legislation sets the limits of YTX contamination in material destined to human consumption (European Communities, 2002).…”
mentioning
confidence: 99%
“…Later, it was separated in its own group, due to different biological origin and different in vivo effects. 4 One of the main differences with OA is that YTX shows no inhibition of protein phosphatase 2A (PP2A). 5 Recently, it has been observed that, in fact, YTX and OA show an immunoregulatory effect over lymphocytes, although through protein kinase C (PKC) mediated mechanisms in the case of YTX and through PP2A mechanisms in the case of OA.…”
Section: −3mentioning
confidence: 99%